Serum Creatinine in Patients with Advanced Liver Disease Is of Limited Value for Identification of Moderate Renal Dysfunction: Are the Equations for Estimating Renal Function Better? - Jillian MacAulay; Kara Thompson; Bryce A Kiberd; David C Barnes; Kevork M Peltekian (Canadian Journal of Gastroenterology)
BACKGROUND: The Cockcroft-Gault formula (CGF) is used to estimate the glomerular filtration rate (GFR) based on serum creatinine (Cr) levels, age and sex. A new formula developed by the Modification of Diet in Renal Disease (MDRD) Study Group, based on the patient’s Cr levels, age, sex, race and serum urea nitrogen and serum albumin levels, has shown to be more accurate. However, the best formula to identify patients with advanced liver disease (ALD) and moderate renal dysfunction (GFR 60 mL/min/1.73 m2 or less) is not known. The aim of the present study was to compare calculations of GFR, using published formulas (excluding those requiring urine collections) with standard radionuclide measurement of GFR in patients with ALD.